Survival in a real-world cohort of patients with transthyretin amyloid cardiomyopathy treated with tafamidis: an analysis from the Transthyretin Amyloidosis Outcomes Survey (THAOS) - García-Pavía, Pablo; Kristen, Arnt; Drachman, Brian; Carlsson, Martin; Amass, Leslie; Angeli, Franca Stedile; Maurer, Mathew S. (Journal of cardiac failure, 2025)
Background - In the pivotal Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR-ACT), tafamidis significantly reduced mortality rates, leading to its approval in many countries for the treatment of transthyretin amyloid cardiomyopathy (ATTR-CM). Real-world evidence on survival in patients with ATTR-CM following tafamidis treatment has not been extensively reported. - Methods and Results - The Transthyretin Amyloidosis Outcomes Survey (THAOS) was a longitudinal, observational, phase 4 study of patients with transthyretin amyloidosis and asymptomatic participants carrying pathogenic transthyretin variants. Patients from THAOS with a predominantly cardiac phenotype at enrollment were included, and survival was analyzed according to tafamidis treatment status (treated or untreated). Results are based on the completed THAOS dataset. In tafamidis-treated (n=587) and tafamidis-untreated (n=854) patients, respectively, median age at enrollment was 77.7 and 76.4 years, 91.8% and 90.0% were male, and 91.8% and 83.8% had wild-type disease. Survival rates (95% CI) at 30 and 42 months, respectively, were 84.4% (80.5-87.7) and 76.8% (70.9-81.7) in tafamidis-treated patients, and 70.0% (66.4-73.2) and 59.3% (55.2-63.0) in tafamidis-untreated patients. Survival rates in genotype subgroups (wild-type and variant) were similar to those of the overall cohort. Survival rates were better in a contemporary cohort, as reflected by a sensitivity analysis performed in patients enrolled after vs before 2019. No new safety signals were identified. - Conclusions - In this real-world cohort of patients with ATTR-CM, survival rates were higher than in ATTR-ACT and consistent with more recent reports, suggesting early diagnosis and treatment with tafamidis has improved life expectancy in ATTR-CM. These results provide further evidence supporting tafamidis’ safety and effectiveness. Trial registration: ClinicalTrials.gov identifier: NCT00628745
Online verfügbar: 21. Juni 2024, Artikelversion: 11. März 2025
Gesehen am 19.08.2025